DIFFERENTIATED APPROACH TO FOREIGN LANGUAGE TRAINING IN NON-LINGUISTIC HIGHER EDUCATIONAL INSTITUTION - Klets, Tatyana; Malysheva, Oksana; Presnyakova, Nadezhda (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2018)
In the Russian system of foreign language education, learner-centred approach is seen as a leading strategic direction designed to ensure self-realization of the learner as a linguistic personality able to interact effectively in the intercultural context. The problem of differentiation is one of the central issues in learner-centred education. In authors’ opinion, the differentiated approach is the most optimal in the conditions of the heterogeneity of the study groups. The article reveals the main characteristics of a differentiated approach as a general methodological principle of teaching, allowing to take into account the individual, intellectual and psychophysiological characteristics of students. The problems, advantages and disadvantages of differentiated education in non-linguistic higher schools are analyzed. The authors of the article examine the essence of multilevel training, define its principles, describe both the external differentiation of students depending on the difference in linguistic competence and the internal differentiation as the organization of the learning process, in which the individual characteristics of students are contemplated in the conditions of a homogeneous group. Generalization of the experience on the afore-mentioned differentiation forms in the system of language training is given as well as some techniques and methods of teaching in multilevel groups are offered.